Mitophagy: A potential therapeutic target for insulin resistance - Ning, Peng; Jiang, Xiaobo; Yang, Jing; Zhang, Jiaxing; Yang, Fan; Cao, Hongyi (Frontiers in Physiology, 2022)
Glucose and lipid metabolism disorders caused by insulin resistance (IR) can lead to metabolic disorders such as diabetes, obesity, and the metabolic syndrome. Early and targeted intervention of IR is beneficial for the treatment of various metabolic disorders. Although significant progress has been made in the development of IR drug therapies, the state of the condition has not improved significantly. There is a critical need to identify novel therapeutic targets. Mitophagy is a type of selective autophagy quality control system that is activated to clear damaged and dysfunctional mitochondria. Mitophagy is highly regulated by various signaling pathways, such as the AMPK/mTOR pathway which is involved in the initiation of mitophagy, and the PINK1/Parkin, BNIP3/Nix, and FUNDC1 pathways, which are involved in mitophagosome formation. Mitophagy is involved in numerous human diseases such as neurological disorders, cardiovascular diseases, cancer, and aging. However, recently, there has been an increasing interest in the role of mitophagy in metabolic disorders. There is emerging evidence that normal mitophagy can improve IR. Unfortunately, few studies have investigated the relationship between mitophagy and IR. Therefore, we set out to review the role of mitophagy in IR and explore whether mitophagy may be a potential new target for IR therapy. We hope that this effort serves to stimulate further research in this area.